Ways to improve tourism transport infrastructure in the Imereti region - Gvantsa Arjevanidze; Teimuraz Kochadze; Izolda Dangadze; Jumber Chogovadze (ეკონომიკური პროფილი)
In the Imereti region, a study of the transport infrastructure of tourism was conducted based on questionnaires and surveys of managerial level specialists and practitioners engaged in the field of transport and tourism. The study demonstrated that the existing approaches in the spheres of tourism and transport in the region cannot promote the rapid development of tourism transport infrastructure. The research showed that the existing approaches in the direction of tourism and transport in the region cannot contribute to the rapid development of tourism transport infrastructure. Studies have the need for undertaking effective measures that can have a positive impact on the development of the tourism transport infrastructure in the region and enhance the attractiveness of the tourism sector.